The evaluation of the ONIOM-EE method for the QM/MM hybrid modeling of HF, CO and CO/HF Clusters - Crous, Werner (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.